2019
DOI: 10.1002/hep4.1310
|View full text |Cite
|
Sign up to set email alerts
|

Who to Test for Hepatitis C Virus in the Middle East and North Africa?: Pooled Analyses of 2,500 Prevalence Measures, Including 49 Million Tests

Abstract: Expanding hepatitis C virus (HCV) treatment coverage is challenged by limited testing and diagnosis. This study assessed the risk of exposure, for the Middle East and North Africa, by population, yields of testing, and program efficiency of testing strategies. A standardized and systematically assembled database of 2,542 HCV antibody prevalence studies on 49 million individuals was analyzed. Random effects meta‐analyses were conducted to estimate pooled measures for risk of exposure, risk ratio (RR) of exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 51 publications
1
27
0
Order By: Relevance
“…The presented evidence attests to the immediate need for prioritizing LRD populations in HCV testing and treatment programs. Recent evidence has also highlighted the program efficiency of this prioritization . It is also clear that interventions, such as testing and treatment, have not yet reached sufficient effectiveness, coverage, and reach to impact HCV epidemiology (apart from Egypt).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presented evidence attests to the immediate need for prioritizing LRD populations in HCV testing and treatment programs. Recent evidence has also highlighted the program efficiency of this prioritization . It is also clear that interventions, such as testing and treatment, have not yet reached sufficient effectiveness, coverage, and reach to impact HCV epidemiology (apart from Egypt).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has also highlighted the program efficiency of this prioritization. (53,54) It is also clear that interventions, such as testing and treatment, have not yet reached sufficient effectiveness, coverage, and reach to impact HCV epidemiology (apart from Egypt). Without timely and effective interventions, elimination of HCV infection and its disease burden by 2030 will not be possible.…”
Section: Discussionmentioning
confidence: 99%
“…The study concluded that testing strategies can be much more efficient through population prioritization by risk of exposure. 26 Despite the most recent U.S. Food and Drug Administration (FDA) approval of DAA in children aged 3 years and above (September 2019) and approval for ages 12 years and above since April 2017, access to treatment is still a major concern driven by the prohibitive prices of DAA in some countries and the lack of policies and strategies addressing linkage to care and elimination in the pediatric population. Adolescents also face particular challenges in terms of access to and quality of care, as they have special needs (including for confidentiality) and may not be reached by mechanisms aimed at children and adults.…”
Section: Elimination Of Hepatitis C Virus In Childrenmentioning
confidence: 99%
“…They multiply and produce viremia in the vertebrates, multiply in the tissues of arthropods, and are passed on to new vertebrates by the bites of arthropods after a period of extrinsic incubation. Research on emerging infectious diseases needs to be identified as a priority in Africa (Petersen et al, 2019;Chemaitelly et al, 2019).…”
Section: Dangerous Viruses In Africamentioning
confidence: 99%